2

WARM COLD

 

 

 

 

f( "'sense'" ) = y('( ))

 

 

f' ( "'sense'" ) = x('( ))

 

 

 

 

 

 

(y,x,z) = { ♂ } <

 

 

( Ψ ( ψ ( ψ' ) ) ) < ♂' = ξ(T) < T(ξ)

 

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

♂(pharoa * mouse) = ♀(amunre)

 

 

 

 

( ♂(upsacespacefish) * ♀(human) ) = ( ♂(animal) * ♀(animal) ) = ξ (family)

 

 

ξ (family) = ξ (tree) = ξ ( T )

 

 

 

 

 

 

_____________________________________________________________________________

 

 

 

 

 

 

[] ∈ { + , - } = { , }

 

 

 

= / ~ = /

 

=> = - / +

 

 

 

lim --> ' O L O '

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

E(potential) = E(kinetic)

 

 

~

 

 

lim E(potential) --> E <-- E(kinetic) mil = lim'

 

=> E ~ E(kinetic) = E(potential)

 

E = f ^ (Ψ) = C * (Ψ) = L * (Ψ)

 

f = 1 / T(s)

 

 

 

 

 

f(Ψ) = (Ψ) * 0 , if 1 = 0

 

 

 

 

 

 

 

 

 

lim ( Ψ ) ∈ { [K] , [A] , [N] , [T] , [n] , [V] , [Ω] }

 

--> ] -s , Ψ , s [ < ∞ / ∞ = ∫ (ψ(0))

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

Exo-Reaction ~ lim (') -> ∞ / 0

 

 

(Exo) = ∫(>)'

 

 

Imagine a particle could become a smaller 'particle'

 

 

 

 

Endo-Reaction ~ lim () -> 0 / ∞

 

 

(Endo) = ∫(<)'

 

 

Imagine that there might is on another way around it once you turn

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

t(ξ) * (t) = (T)

Imagine ∫t(ξ) as a factor of time win, (t) as an local event of time, (T) as an all time event of Time

 

 

 

 

 

E = ξ' ~ t(ξ)

 

ξ = Δy * Δx * Δz

 

Imagine ξ actually rely'ing in and around over time win

 

 

 

 

 

t(y') ∈ = [ 3 , +s [

t(x') ∈ = [ 6 , +s [

 

t(z') ∈ = ] 36 , +s [

 

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

Δv = ∫0 / t^t(Δy * Δx)

 

Imagine turning a knob at your radio

 

 

 

 

 

 

 

Δa = ∫0 / t^t(Δy * Δx)

 

 

 

 

 

Δδ = ∫0 / t^t(Δy * Δx)

 

Imagine a candlelight burning

 

 

 

 

 

 

δ' ∈ ^(0) = { π }

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

T = t(nutshell)

 

 

 

1/0 = 0/1

 

 

 

 

(T) = [s]

 

 

 

 

 

 

t(ξ) < T(ξ)

 

=>

 

t'(ξ) > T'(ξ)

 

 

 

 

 

t(ξ) = T(ξ)

 

 

 

 

 

[m] = ξ'

[kg] = ξ'

[s] = ξ'^(')

 

 

 

 

 

δ = Ψ = '

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

ξ() = '

 

= { æ ( t ) }

 

 

 

 

ξ' = ξ < { } < f( T )

 

 

 

 

 

 

 

( ξ ) < ξ(T) = { æ'() }

 

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

x = y

 

 

~

 

=

 

 

 

 

 

 

 

 

 

 

( T ( Ψ ) ) = *

 

 

 

 

 

 

 

 

=> t^3

T( ∫ Ψ ) = *

Δ F

 

 

 

 

 

 

+ t - t

= = (+) * ξ ~ = = (-) * ξ

Δ E Δ E

 

 

 

 

 

 

 

 

 

=> () = (-) * T ~ () = (+) * T

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

α = (Ψ) > = β

 

 

 

 

 

 

ξ(T) > (Ψ) >

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

 

5 > ξ() = (4) > (4') = ♂' = ♂(C) > 2

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

{ 0 , 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 } (♀') =

 

{ 4 , 3 , 2 , 1 , 0 , 9 , 8 , 7 , 6 , 5 } ()

 

 

 

~

 

 

{ 9 , 8 , 7 , 6 , 5 , 4 , 3 , 2 , 1 , 0 } (♂') =

 

{ 5 , 6 , 7 , 8 , 9 , 0 , 1 , 2 , 3 , 4 } ()

 

 

 

 

 

 

 

 

 

♀[(3) *(6)] = { 0,1,2,3,4,5,6,7,8,9 }

 

~

 

 

♂[(6) *(3)] = { 9,8,7,6,5,4,3,2,1,0 }

 

 

 

 

 

 

 

 

=> 5' = 9 ~ 4' = 0

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

{ 0 , 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 } () =

 

{ 9 , 8 , 7 , 6 , 5 , 4 , 3 , 2 , 1 , 0 } ()

 

 

 

 

=> 1' = 0

2' = 1

3' = 2

4' = 3

5' = 4

 

6' = 5

7' = 6

8' = 7

9' = 8

1' = 0

 

 

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

 

(ξ) ------------------> (ξ') <----------------------------------- (ξ'')

 

 

' (ξ) ------------------------> '(ξ') <---------------------------- ' (ξ'')

 

 

''(ξ) -----------------------------> ''(ξ') <---------------------- ''(ξ'')

 

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

 

x = y

 

 

~

 

=

 

 

 

 

lim (9) = ∫(8) = ∫∫(7 ) = ∫∫∫(6) = ∫∫∫∫(5) --> (4)

 

lim (4) = '(3) = ''(2) = '''(1) = ''''(0)

 

 

<=> '''''(-1) --> (4)

 

 

=> ''''''(-2) --> (4)

=> '''''''(-3) --> (4)

=> ''''''''(-4) --> (4)

 

=> '''''''''(-5) --> (4)

=> ''''''''''(-6) --> (4)

=> '''''''''''(-7) --> (4)

=> ''''''''''''(-8) --> (4)

=> '''''''''''''(-9) --> (4)

 

 

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

3' < 6'

 

 

3 < 6

 

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

7 < 9

 

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

 

C(ξ)

 

 

*

*

*

*

*

*

*

*

*

*

*

*

*

*

* *

* * *

* * * *

* * * * *

* * * * * *

* * * * * * *

* * * * * * * C(ξ)

 

 

C(ϰ) = '() = '()

 

 

C(ψ) = () = ()

 

 

 

 

C(ϰ) > C(ψ)

 

 

 

 

 

 

 

 

'() = '() =() = (♀)

 

 

 

=> C(t) = L(t)

 

 

 

 

 

L(ϰ) < L(ψ)

 

 

 

 

 

 

 

_______________________________________________________________________________

 

 

 

 

 

 

 

' = T(5,6,7,8,9)

 

 

 

' = T

 

 

' =